Supply Chain Transparency Research: A Bibliometric Analysis - Loso Judijanto (Westscience Press, 2026)
Supply chain transparency has become one of the key topics in recent years due to the increasing emphasis on sustainability, traceability, digital transformation, and accountability in global supply networks. The widespread application of advanced technologies including blockchain, Internet of Things (IoT), and smart contracts has led to a growing body of literature on studying the benefits of supply chain transparency and its role in enhancing performance and resilience. This paper aims at revealing the intellectual structure, evolution, collaboration pattern, and future directions of supply chain transparency research by employing bibliometrics. Data was obtained from Scopus databases and then analyzed with the help of bibliometric methods supplemented by VOSviewer. Publication analysis, authorship analysis, institutional collaboration, country collaboration, citation analysis, keyword analysis, overlay visualization, and density visualization will be employed in the process of data analysis. It can be found that the most dominating themes among supply chain transparency literature include blockchain, supply chain management, sustainability, traceability, and digital transformation. India and China became major players in the network of international collaboration, while some institutions functioned as knowledge hubs. Most citations were achieved by papers discussing blockchain-based sustainable supply chains and frameworks for implementing transparency. Keyword evolution further demonstrates a shift from operational visibility toward integrated digital ecosystems emphasizing sustainability, circular economy, food safety, and intelligent supply chain governance.